Research Trends in Critical Thinking for Science Education: A Mixed Method Approach Using SLR and Bibliometrics (2014-2024) - Sarawati, Tia; Natadiwijaya, Ismail Fikri (Proceeding International Conference on Religion, Science and Education, 2025)
A Critical thinking skills play a crucial role in the trends of science education, particularly in 21st-century learning. Numerous researchers have investigated critical thinking abilities to gain deeper insights into the direction of education in this century. The development and application of critical thinking in science education have spanned from 2014 to 2024. This study employs a mixed-method approach, combining Systematic Literature Review (SLR) and Bibliometric Analysis. The bibliometric research follows stages aligned with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. The study encompasses students from various educational levels, including elementary, junior high, and senior high school, as well as diverse instructional methods that integrate critical thinking techniques. The research employs content analysis, involving the description and analysis of data with the aid of VosViewer and Microsoft Excel. The articles analyzed comprise 120 publications obtained through the Publish or Perish search engine from the Scopus and Google Scholar databases. The findings indicate that studies on critical thinking map the relationships between keywords based on the four color clusters in VosViewer visualizations, including critical thinking, science, education, problem-based learning, and curriculum. These keywords are interconnected and reflect the central themes in educational research. The study's findings are anticipated to provide valuable insights for other researchers regarding aspects such as the number of publications, country of origin, publication types, research methods, research subjects, instruments used, and instructional interventions.